(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article presents an analysis of current and innovative projects for the development of tourism in the medical field of the Republic of Tajikistan for the period 2018-2022. from the business community and with the support of regional executive authorities. Problems are identified and prospects for further development of medical and health tourism in the region are proposed. Assumed innovative pedagogical technologies for the study of the organization of the educational process and the training of highly specialized tourism personnel in the current conditions of economic development. Also, the development and implementation of the project International Medical Cluster of the Republic of Tatarstan.